Psychopathy as a Predictor Variable of The Disposition to Steal - Garcia Cadena, Cirilo Humberto; Valle, Adrián; Daniel, Leopoldo; Grimaldo, Norma; Grimaldo, Brenda; Calderón, Chriztian (2017)
ABSTRACT: The aim of this study was to compare the capacity of psychopathy and some socio-demographic variables in the prediction of the disposition to steal. The sample was composed of 100 prisoners (86 men and 14 women; M = 30.21 years, SD = 8.42) and 100 participants from general community (86 men and 14 women; M = 26.86 years, SD = 7.31). Psychopathy and disposition to steal were assessed through self-report scales and several multiple-regression techniques were performed. Results show that socio-demographic variables are significant predictors of the disposition to steal only in the group of prison population (effect size was small, R² = 3.20%). The psychopathy is a significant predictor of the disposition to steal among prison population (large effect size: R² = 72.80%) as well as among participants from the general community (large effect size: R² = 67.90%). The interpersonal dimension of psychopathy has a greater predictive value (R² = 75.30%) than the affective dimension (R² = 23%) among prisoners; nevertheless, the predictive values of the affective dimension (R² = 51.20%) and the interpersonal dimension (R² = 63.40%) are similar among participants from the general community. The implications of these findings for diagnosis, intervention and future research are discussed. KEYWORDS: Psychopathy, Steal Disposition, Prison Population, General Community.